Tantangan dalam Membelajarkan Matakuliah Seminar Pendidikan Biologi - Herawati Susilo; Ahmad Kamal Sudrajat (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The achievement of the seminar course is that students are expected to be able to discuss a Biology Education/Biology topic in depth and write it into a work in the form of problem solving ideas. The idea is packaged into one of Student Creativity Program/SCP (Program Kreativitas Mahasiswa/PKM) which was developed for one semester in the Biology Education Seminar course. Descriptive research was conducted in the even semester of 2017/2018 in two classes consisting of 16 and 13 students of S1 Biology Education class of 2015. The results showed that each student managed to collect the PKM script consisting of 9 scripts of PKM Penelitian (Research SCP), 9 scripts of PKM Gagasan Tertulis (Written Ideas SCP), 7 scripts of PKM Kewirausahaan (Enterpreunership SCP), 2 scripts of PKM Pengabdian pada Masyarakat (Community Service SCP), and 2 scripts of PKM Karsa Cipta (Creative Work SCP). The topics of the collected PKM consists of 3 scripts on biology education topics, 23 scripts on biology topics, and 3 scripts on neither biology nor biology education topics. The scripts that were collected had not reached the expectation because most of the students chose topics in biology, not in biology Education. The quality of the submitted scripts has not met expectations because it was doubted whether they could compete to win the grant from the government. Based on the result, the learning challenge in this course is to improve the interest of the students to chooce biology education topics and the quality of PKM scripts so that they could compete to win the grant.